Developing effective paragraph writing skills - Sucharat Rimkeeratikul; Monnipha Somphong; Virasuda Sribayak; Kittitouch Soontornwipast; Thanom Tiensawangchai; Ketvalee Porkaew; Vajjaganh Suriyatham; Sumon Kunwongse (Bangkok : Thammasat University Press, 2019)
With a collaboration among Language Institute Thammasat University faculty members and a textbook writing grant from the Language Institute Thammasat University, this textbook Developing Effective Paragraph Writing Skills is intended as a text for a course in English writing at tertiary level. It is designed to help Thai EFL learners from different disciplines improve their academic writing skills which are essential for their higher education. It offers an outline account of the most important and central writing constructions in English. With clear step-by-step instructions in paragraph writing, Developing Effective Paragraph Writing Skills builds writing, reading, and critical thinking skills, and also combines comprehensive grammar review with an introduction to writing. Constant reinforcement is provided through examples and exercises.
Includes bibliographical references
Keywords: English language -- Writing; English language -- Rhetoric